A study of abstracts in Anthropology: The heterogeneity within the field(s) - Gil, Beatriz; Aranha, Solange [UNESP] (FapUNIFESP (SciELO), 2017)
This paper analyzes the genre research article abstract across Anthropology. Twenty-four abstracts were selected from two Anthropological journals. The corpus was analyzed based on Gil's model (2011) and the concepts of hedges and boosters from Hyland (1998, 2002, 2011). The results indicate that the journals occupy different boarders within the subject. JHE is aimed at hard and quantitative researches, whereas CA is focused on interpretative and qualitative researches. These differences shape the materialization of the abstracts, supporting the claim that the boarders infl uence directly in the constitution of the academic genres, corroborating Bazerman's notion of tipification (2006, 2009).
Um estudo do gênero abstract na disciplina de Antropologia: A heterogeneidade da(s) área(s)
Keywords: Abstracts; Boosters; Hedges; Stance